Dating the funerary use of caves in Liguria (northwestern Italy) from the Neolithic to historic times: Results from a large-scale AMS campaign on human skeletal series. (20th January 2020) - Sparacello, V.S.; Varalli, A.; Rossi, S.; Panelli, C.; Goude, G.; Palstra, S.W.L.; Conventi, M.; Del Lucchese, A.; Arobba, D.; De Pascale, A.; Zavattaro, M.; Garibaldi, P.; et al.
Abstract: The multidisciplinary research team of this new project aimed at the chronological, anthropological and funerary behavior characterization of the skeletal remains unearthed from various caves in western Liguria (northwestern Italy) between the mid-1800s and the 1990s. Most of the burials and scattered bone assemblages were excavated prior to the development of modern stratigraphic methods, or come from disturbed contexts, often resulting in a vague chrono-cultural attribution. We present here the results of a systematic dating project that produced 130 new AMS dates on human bone samples (documented burials or individuals from scattered remains) from sixteen Ligurian caves, including most of the skeletal series from renowned sites such as Arene Candide Cave and Grotta Pollera. Results highlighted the funerary use of these caves from the last quarter of the sixth millennium BCE to the Common Era, with the majority of results clustering in the first half of the fifth millennium BCE. These dates allow for an initial assessment of patterns in Neolithic mortuary use of Ligurian caves, and aided in particular the characterization of funerary practices during the Square Mouthed Pottery culture.